Empire and image of power in Late Antiquity: 'De regno' by Synesius of Cyrene between the 'Dominate' and the 'Principate' - Jerce da Costa Junior, Cesar Luiz (Romanitas - Revista de Estudos Grecolatinos, 2021)
This paper will present some considerations about the construction of the image of power and princely conduct thought by Synesius of Cyrene in his treatise De regno, written during his stay at the court of emperor Arcadius. Synesius presents himself as a hellenistic author par excellence, mixing political and philosophical elements in a mosaic of ideas with the reforming purpose of reestablishing the majesty of the Empire. From the author's text, we defend the following conclusion: the new image of power offered to Arcadius should move away from the Dominate and get closer to the Principate model of the first centuries of the Cristian Era.
Keywords: Synesius of Cyrene; Image; Power; Dominate; Principate